Girls' friendships as habitus in an elite, middle-class secondary school in Ireland. (9th August 2019) - Hamilton, Miriam; Deegan, Jim
ABSTRACT: This study examines gendered and classed friendships in a predominantly middle-class, girls' secondary school in the southern region of the Republic of Ireland. Bourdieu's (1977) concept of habitus, interactively, with Gidden's (1984) concept of practical consciousness, and Gambetta's (1987) intentional rational choice informed the conceptual framework for the study. Narrative sources yielded data about girls' friendships and peer interactions inside and outside of school. The social class and habitus of each of the girls mediated their friendship formation and friendship choice. Data sources highlight that the middle-class girls' friendships were situated in fluid and multiple cliques; given their hegemonic positionality within the school. Contrastingly, working-class girls' friendships were situated in a contained and single clique, often evidenced by their resistance to the institutional habitus. The ways in which these peer friendships operated as powerful shapers of the girls' actions and identities is discussed. This paper provides examples of the nuanced ways that girls' friendships are developed and maintained based on conformity or resistance to the school norms and expectations of academic success. Importantly, findings evidence the differentiated and instrumental use of friendships among the middle-class and working-class girls in a competitive, elite school setting.